Factors Associated with Subjective Health Status among People with Spinal Cord Injury: An Application of the International Classification of Functioning, Disability and Health Model. - Haesun Lee; Hye Jin Nam; Ju Young Yoon (Research in Community & Public Health Nursing (RCPHN), 2025)
Purpose: This study aimed to identify factors influencing subjective health status among individuals with spinal cord injury (SCI) using the International Classification of Functioning, Disability and Health (ICF) model. Methods: This study analyzed secondary data from the 2021 Survey on the Status and Needs of Individuals with SCI conducted by the Korea Spinal Cord Injury Association. A hierarchical multiple regression analysis was conducted in four steps. Independent variables included sociodemographic factors, satisfaction with medical services (environmental factor), the need for weight control, the need for nutritional education, the need for dietary management, and disability acceptance (personal factors) along with exercise and activity of daily living (activity and participation factors). These factors were added sequentially at each step based on the ICF model. Results: A total of 513 participants were analyzed in this study, with an average subjective health status of 5.51±2.39. Higher satisfaction with medical services (β=.27, p<.001), frequent exercise (β=.19, p=.008), and a greater level of activities of daily living (β=.02, p<.001) were significantly associated with improved subjective health status. Conversely, a lower need for nutritional education (β=-.25, p=.042) was negatively associated. Conclusion: This study highlighted satisfaction with medical services, nutrition education needs, exercise frequency, and activities of daily living as important factors. These findings provide insight into how the health status of individuals with SCI can be enhanced through targeted interventions and support from healthcare providers.